2021
DOI: 10.1371/journal.pone.0257458
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of vascular surgery teleconsultation during the COVID-19 pandemic: Insights from the outpatient vascular clinics in a tertiary care hospital in Qatar

Abstract: Background The COVID-19 pandemic has sparked a surge in the use of virtual communication tools for delivering clinical services for many non-urgent medical needs allowing telehealth or telemedicine, to become an almost inevitable part of the patient care. However, most of patients with vascular disease may require face-to-face interaction and are at risk of worse outcomes if not managed in timely manner. Objective We aimed to describe the utilization of telemedicine services in the outpatient vascular surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…After review, 12 studies were included, reporting data on 27,307 patients12–23( Table 1 ). One study 14 evaluating teleconsultation utilization rates reported data on 23,894 patients and was the largest study by far. Eleven studies were retrospective cohort studies12–19,21–23, and one was a case series 20 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After review, 12 studies were included, reporting data on 27,307 patients12–23( Table 1 ). One study 14 evaluating teleconsultation utilization rates reported data on 23,894 patients and was the largest study by far. Eleven studies were retrospective cohort studies12–19,21–23, and one was a case series 20 .…”
Section: Resultsmentioning
confidence: 99%
“…The other four studies were undertaken in Qatar, Australia, Colombia and China14,15,19,22. Eight studies looked at data collected during the early period of the COVID-19 pandemic (between March 2020 to September 2020) 12 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , one study looked at data collected between April and June 2021 19 , and two studies looked at data collected throughout the pandemic 14 , 18 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations